The influence of organisational culture on the Total Quality Management programme performance - José L. Roldán; Antonio L. Leal-Rodríguez; Antonio G. Leal (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2012)
This paper aims to examine the relationships between different types of cultures and effectiveness in Total Quality Management (TQM) implementation. Using Cameron's framework, we have tested the connection between a quality culture taxonomy and TQM programme performance using data from a survey carried out with 113 Spanish companies that have implemented TQM systems. A structural equation modelling is proposed to assess the links between both types of constructs using the Partial Least Squares (PLS) technique. The most substantial results confirm, in the sample analysed, the relationship between quality culture types and the TQM programme performance, and there being different influence levels of the quality cultures.
Keywords: M10; M14; L25; C31; 650; quality culture; performance; total quality management